2017
DOI: 10.1021/acs.jpclett.7b02989
|View full text |Cite
|
Sign up to set email alerts
|

Electric Fields and Fast Protein Dynamics in Enzymes

Abstract: In recent years, there has been much discussion regarding the origin of enzymatic catalysis and whether including protein dynamics is necessary for understanding catalytic enhancement. An important contribution in this debate was made with the application of the vibrational Stark effect spectroscopy to measure electric fields in the active site. This provided a window on electric fields at the transition state in enzymatic reactions. We performed computational studies on two enzymes where we have shown that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 25 publications
3
55
0
Order By: Relevance
“…In particular, for the enzymes lactate dehydrogenase (LDH) and purine nucleoside phosphorylase (PNP), for which it has been shown that fast dynamics is part of the reaction mechanism, the electric field reaches its most favorable value in the active center for the transition state. These results seem to reconcile two theories, apparently antagonistic, which attribute the origin of the catalysis to the electrostatic preorganization or to the fast protein dynamics …”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…In particular, for the enzymes lactate dehydrogenase (LDH) and purine nucleoside phosphorylase (PNP), for which it has been shown that fast dynamics is part of the reaction mechanism, the electric field reaches its most favorable value in the active center for the transition state. These results seem to reconcile two theories, apparently antagonistic, which attribute the origin of the catalysis to the electrostatic preorganization or to the fast protein dynamics …”
Section: Resultssupporting
confidence: 51%
“…These results seem to reconcile two theories, apparently antagonistic, which attribute the origin of the catalysis to the electrostatic preorganization or to the fast protein dynamics. [60]…”
Section: Implications In the De Novo Design Of A Kemp Eliminasementioning
confidence: 99%
“…Below each structure, a label of n-m is given in blue; n denotes the group number (reflecting the type of VSE probe bond and m is the number of the molecule within this group. Vibrational probe labels with superscripts are taken from the literature (a [95], b [5,96], c [96], d [5,7,25,28], e [5,13,97], f [13], g [13,26], h [14,15,98]). The corresponding performance score as VSE probe is given in purple.…”
Section: Resultsmentioning
confidence: 99%
“…Given a simplified electrostatic description of non-covalent interactions between the vibrational probe and surrounding molecules, the strength of these intermolecular interactions can be assessed by the electric field a target chemical bond feels, as revealed by the VSE [5,13]. The VSE has been extensively applied to study the non-covalent interactions in different types of chemical systems and environments including proteins/enzymes [6][7][8]10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], nucleic acids [34,35], ionic liquids [36,37], biological membranes [38], electrochemical interfaces/surfaces [12,[39][40][41][42][43], and polymers [3,44,45]. Recently, the range of applications has been extended to the investigation of water clusters [46,47] and molecular solids [48].…”
Section: Introductionmentioning
confidence: 99%
“…[42] It has also been shown that, in some reactions, the fast motions lead to a configuration which is electrostatically favourable for catalysis. [43] In this work the effect of the intensity and orientation of an external electric field have been analyzed. We have found that catalysis is very sensitive to the intensity of the field, but much less to its orientation.…”
Section: Implications In the De Novo Design Of A Kemp Eliminasementioning
confidence: 99%